The meaning of institutionalisation to older Africans: a case study of a Zimbabwean old people’s home - Hungwe, Chipo (Electronic Journal of Applied Psychology, 2016)
Institutionalisation is foreign to older persons in Africa. It invokes negative feelings on those institutionalised. These negative feelings include those of guilt, neglect and abandonment by relatives, regret and powerlessness. While institutionalisation cannot be avoided especially for destitute individuals, it has depersonification effects, some of which can be avoided if staff at the institution can be more accommodative and some rules changed/repealed to allow the older persons to live respectable existences. The intentional and sometimes calculated exercise of power by staff in determining all the activities of the older persons feeds on to older people‟s feelings of powerlessness. However, since the older persons cannot live without the institution they have to gratefully accept their situation dealing with each day as it comes, waiting for death.